Lichen sclerosus of the oral mucosa: clinical and histopathological findings. Review of the literature and a case report. (4th July 2018) - Matela, Anna-Maija; Hagström, Jaana; Ruokonen, Hellevi
Abstract: Objectives: Lichen sclerosus (LS) is a rare, chronic mucocutaneous disease that most frequently affects the female genital area. Oral manifestations are seldom detected; only 36 well-documented and histopathologically verified oral LS cases have been published. Materials and methods: Here we describe one patient affected by oral (LS) and review of the literature 1957–2017. Results: Findings in our review suggest a female to male ratio of 1.64:1. It is most commonly diagnosed at the age of 10–29 years (46%). Oral LS can appear as symptomless, irregular-shaped, porcelain-white and flat lesions situated asymmetrically. Lesion is commonly sole, well-demarcated area and its size varies from 2 mm (small macula) to 7 cm (large plaque). The most common sites in the oral cavity include the labial mucosa, lips and gingiva. The histopathological criteria include atrophy and sometimes hyperkeratosis of the epithelium, hydropic degeneration of basal cells, hyalinization of the lamina propria, lymphocyte infiltration beneath the zone of hyalinization and scantiness of elastin. Surgical excision is an effective treatment for small lesions; intralesional triamcinolone or corticosteroid injections are used for larger lesions. Conclusions: Oral LS may be under-recognized due to its asymptomatic nature and rarity.